A LaOCl-ZnO composite catalyst, LaOCl-ZnO hydrogel, and preparation method and application thereof

By depositing nano zinc oxide in situ on LaOCl, the LaOCl-ZnO composite catalyst was prepared, which solved the problem of low uranium removal efficiency of existing photocatalysts and achieved efficient and low-cost uranium removal effect.

CN118045637BActive Publication Date: 2025-03-21NORTHEAST GASOLINEEUM UNIV
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
CN202410204134.9
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-02-23
Publication Date
2025-03-21
Estimated Expiration
2044-02-23

AI Technical Summary

Technical Problem

The existing photocatalysts have low efficiency in removing uranium, and the preparation process of nano zinc oxide as an alternative material is complex, energy consumption, and a small range of materials application.

Method used

The LaOCl-ZnO composite catalyst was prepared by ultrasonic-assisted in-situ deposition method. By depositing nano zinc oxide in situ on LaOCl, the photoresponse range is broadened, the photogenerated electron hole recombination problem is suppressed, and the photocatalytic efficiency is improved.

Benefits of technology

The removal rate of uranium is significantly improved. The adsorption of uranium by LaOCl-ZnO composite catalyst under visible light irradiation is as high as 384.5 mg/g, with a removal rate of 96.1%. The preparation process is simple and low-cost, and it is suitable for large-scale production.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN118045637B_ABST
    Figure CN118045637B_ABST
Patent Text Reader

Abstract

The present invention relates to a LaOCl-ZnO composite catalyst, a LaOCl-ZnO hydrogel, and a preparation method and application thereof. The preparation method of the LaOCl-ZnO composite catalyst comprises: calcining lanthanum chloride in an air atmosphere to obtain LaOCl; mixing LaOCl and zinc nitrate uniformly under ultrasonic conditions with water to obtain a mixed solution, adjusting the pH of the mixed solution to 11-13 with a sodium hydroxide solution and reacting under stirring conditions, and then standing, centrifuging, washing and drying to obtain the LaOCl-ZnO composite catalyst. The LaOCl-ZnO composite catalyst prepared by the present invention has a strong photocatalytic redox ability, and the composite structure increases the visible light catalytic activity. The LaOCl-ZnO composite catalyst has great application prospects in photocatalytic treatment of radionuclides.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of photocatalytic materials, and in particular to a LaOCl-ZnO composite catalyst, a LaOCl-ZnO hydrogel, and a preparation method and application thereof. Background Art

[0002] In recent years, the international community has actively carried out research on the enrichment and separation technology of uranium in wastewater systems. Among them, the adsorption method has become one of the main methods for removing uranium from wastewater due to its advantages such as simple operation, low cost and environmental friendliness. However, the adsorption method is still limited by the poor adsorption performance and low selectivity of the adsorbent. Photocatalytic technology has become one of the effective ways to solve this problem and repair uranium-containing wastewater. Photocatalytic treatment of uranium-containing wastewater has the advantages of good selectivity, high efficiency and rapidity, non-toxicity and mild reaction conditions. It can reduce the soluble U(VI) in the solution to solid U(IV) to achieve uranium removal, and has good prospects in the field of uranium wastewater remediation. At present, a large number of photocatalyst materials have been used for the enrichment and separation of uranium nuclides in uranium-containing wastewater. Nano zinc oxide is considered to be an excellent photocatalytic material that can replace titanium dioxide due to its low cost, easy preparation and environmental friendliness, but its efficiency in removing uranium as a photocatalyst is low.

[0003] In summary, it is very necessary to provide a LaOCl-ZnO composite catalyst, LaOCl-ZnO hydrogel, and a preparation method and application thereof. Summary of the invention

[0004] In order to solve one or more technical problems existing in the prior art, the present invention provides a LaOCl-ZnO composite catalyst, LaOCl-ZnO hydrogel and a preparation method and application thereof. The LaOCl-ZnO composite catalyst material and LaOCl-ZnO hydrogel prepared by the present invention have strong photocatalytic redox ability, and the composite structure increases the visible light catalytic activity. The LaOCl-ZnO composite catalyst material and LaOCl-ZnO hydrogel have good application prospects in photocatalytic treatment of radionuclides.

[0005] In a first aspect, the present invention provides a method for preparing a LaOCl-ZnO composite catalyst, the method comprising the following steps:

[0006] (1) calcining lanthanum chloride in an air atmosphere to obtain LaOCl;

[0007] (2) LaOCl and zinc nitrate are uniformly mixed with water under ultrasonic conditions to obtain a mixed solution, the pH of the mixed solution is adjusted to 11-13 with a sodium hydroxide solution and reacted under stirring conditions, and then allowed to stand, centrifuged, washed and dried to obtain a LaOCl-ZnO composite catalyst.

[0008] Preferably, the calcination temperature is 550°C to 700°C, preferably 650°C, the calcination time is 1.5 to 2.5 hours, preferably 2 hours; the zinc nitrate is zinc nitrate hexahydrate; the molar ratio of LaOCl to zinc nitrate is 1:(0.5 to 2); and / or the concentration of the sodium hydroxide solution is 0.1 to 0.3 mol / L.

[0009] Preferably, the standing time is 12 to 30 hours, preferably 12 to 24 hours; the centrifugal speed is 7000 to 10000 r / min, and the centrifugal time is 4 to 8 minutes, preferably, the centrifugal speed is 8000 r / min, and the centrifugal time is 5 minutes; the washing is performed using water and / or anhydrous ethanol; and / or the drying temperature is 50 to 80°C, preferably 60°C.

[0010] In a second aspect, the present invention provides a LaOCl-ZnO composite catalyst prepared by the preparation method described in the first aspect of the present invention.

[0011] The third aspect of the present invention provides the use of the LaOCl-ZnO composite catalyst prepared by the preparation method described in the first aspect of the present invention in catalytic reduction of uranium.

[0012] The present invention provides a method for preparing LaOCl-ZnO hydrogel in a fourth aspect, the method comprising the following steps:

[0013] (a) using water to uniformly disperse the LaOCl-ZnO composite catalyst prepared by the preparation method described in the first aspect of the present invention by ultrasonication to obtain a LaOCl-ZnO dispersion;

[0014] (b) adding sodium alginate to the LaOCl-ZnO dispersion and mixing them uniformly to obtain a LaOCl-ZnO / sodium alginate solution, then dropping the LaOCl-ZnO / sodium alginate solution into a calcium chloride solution and allowing the solution to stand, and finally washing and drying to obtain a LaOCl-ZnO hydrogel.

[0015] Preferably, the concentration of the LaOCl-ZnO dispersion is 0.0015-0.0025 g / mL, preferably 0.002 g / mL; the mass ratio of the LaOCl-ZnO composite catalyst in step (a) to the sodium alginate in step (b) is 1:(8-12), preferably 1:10; the mass fraction of calcium chloride in the calcium chloride solution is 1-4%, preferably 2%-3%; and / or the standing time is 4-8 h, preferably 6 h.

[0016] In a fifth aspect, the present invention provides a LaOCl-ZnO hydrogel prepared by the preparation method described in the fourth aspect of the present invention.

[0017] In a sixth aspect, the present invention provides the use of the LaOCl-ZnO hydrogel prepared by the preparation method described in the fourth aspect of the present invention in the catalytic reduction of uranium.

[0018] Preferably, LaOCl-ZnO hydrogel is added to a U(VI) solution and adsorbed under visible light irradiation to achieve catalytic reduction of uranium; the concentration of the U(VI) solution is 20 to 700 mg / L; the adsorption time is 5 to 420 min; the adsorption capacity of LaOCl-ZnO hydrogel for uranium is obtained by the following formula:

[0019] Q e =(C0-C e )×V / m

[0020] Among them, Q e is the adsorption capacity, C0 is the initial concentration of U(VI), in mg / L, C e is the adsorption equilibrium concentration of U(VI), in mg / L, V is the volume of U(VI) solution, in L, and m is the mass of LaOCl-ZnO hydrogel, in g;

[0021] The removal rate of uranium by LaOCl-ZnO hydrogel is obtained by the following formula:

[0022]

[0023] Where C0 is the initial concentration of U(VI), C e is the adsorption equilibrium concentration of U(VI).

[0024] Compared with the prior art, the present invention has at least the following beneficial effects:

[0025] (1) The LaOCl-ZnO composite catalyst prepared by the present invention has excellent photocatalytic performance. The present invention broadens the light response range by in-situ depositing nano zinc oxide on LaOCl, effectively suppresses the problem of photogenerated electron-hole recombination, improves the photocatalytic efficiency, and significantly improves the removal rate of uranium.

[0026] (2) Compared with the hydrothermal method, the in-situ deposition method used in the present invention to prepare the LaOCl-ZnO composite catalyst does not require high temperature and high pressure conditions; compared with the calcination method, the crystal structure is controllable.

[0027] (3) The LaOCl-ZnO composite catalyst prepared by the present invention has good crystallization effect, and the ultrasound-assisted method promotes the uniform growth of ZnO on the LaOCl surface.

[0028] (4) The LaOCl-ZnO composite catalyst prepared by the present invention has good performance in photocatalytic reduction of uranium. Currently, the application of LaOCl-ZnO composite catalyst in the field of photocatalytic reduction of uranium has not been reported. In addition, the method for preparing LaOCl-ZnO composite catalyst has the advantages of simple and convenient operation, low cost, low energy consumption and mild conditions, which is conducive to large-scale production.

[0029] (5) In view of the problem that the existing photocatalysts are generally powder materials that are difficult to recycle and easily cause secondary pollution, the present invention adopts sodium alginate (SA). Sodium alginate is a natural anionic polysaccharide with rich functional groups on the surface and has the characteristic of easy gelation. The present invention adopts the "embedding" strategy for the first time to prepare the LaOCl-ZnO composite catalyst into LaOCl-ZnO hydrogel, which can solve the problem of difficult recycling of powder materials on the one hand, and further reduce the leaching of ions in the photocatalyst on the other hand, so as to maintain the integrity of the photocatalyst, exert its role to a greater extent, and further improve the photoreduction efficiency of the LaOCl-ZnO composite catalyst to uranium. BRIEF DESCRIPTION OF THE DRAWINGS

[0030] Figure 1 It is a schematic diagram of the process of preparing LaOCl-ZnO composite catalyst and LaOCl-ZnO hydrogel according to the present invention;

[0031] Figure 2 This is an XRD comparison diagram of LaOCl prepared by the one-step calcination method of the present invention and the raw material LaCl3;

[0032] Figure 3 is the XRD analysis spectrum of LaOCl prepared at different calcination temperatures in Examples 1 to 4 of the present invention;

[0033] Figure 4 It is the XRD analysis spectrum of the LaOCl-ZnO composite catalyst prepared at different La:Zn molar ratios in Examples 5 to 8 of the present invention;

[0034] Figure 5 is the SEM-EDS image of the LaOCl-ZnO composite catalyst prepared in Examples 5 to 8 of the present invention; Figure 5 In the figure, (a) to (f) are SEM images of LaOCl (calcined at 650 °C for 2 h), ZnO, LaOCl-ZnO-0.5, LaOCl-ZnO-1, LaOCl-ZnO-1.5 and LaOCl-ZnO-2, respectively, and (g) is the EDS spectrum of LaOCl-ZnO-1.5;

[0035] Figure 6 is a SEM image of SA / LaOCl-ZnO-1.5 hydrogel microspheres prepared in Example 9 of the present invention;

[0036] Figure 7 is a graph showing the photocatalytic performance characterization results of the LaOCl-ZnO composite catalysts prepared in Examples 5 to 8 of the present invention; Figure 7 In the figure, (a) is the EIS curve of LaOCl (calcined at 650℃ for 2h), ZnO and LaOCl-ZnO-1.5; (b) is the PL fluorescence spectrum; (c) is the Tauc curve;

[0037] Figure 8 is a graph showing the photocatalytic performance characterization results of the LaOCl-ZnO composite catalysts prepared in Examples 5 to 8 of the present invention; Figure 8 In the figure, (a) is the Mott-Schottky curve of LaOCl prepared by calcination at 650℃ for 2h at different frequencies; (b) is the Mott-Schottky curve of ZnO at different frequencies; (c) is the Mott-Schottky curve of LaOCl-ZnO-1.5 at 1000Hz; (d) is a schematic diagram of the energy band structure of LaOCl (calcined at 650℃ for 2h), ZnO and LaOCl-ZnO-1.5;

[0038] Fig. 9 This is the result diagram of the effect of different pH values ​​on the adsorption of uranium by SLZ-1.5 under light and dark control;

[0039] Fig.10 The figure is the result of the adsorption-photocatalytic kinetics and isotherm study of uranium by SLZ-1.5 under light and dark control; in the figure, (a) is the adsorption kinetics curve; (b) is the pseudo-second-order kinetics fitting curve; (c) is the Langmuir and Freundlich adsorption isotherm fitting curve under light conditions; (d) is the Langmuir and Freundlich isotherm fitting curve under no light conditions;

[0040] Fig.11 This is the result of the cyclic adsorption and desorption test of uranium by SLZ-1.5 under light and dark contrast. DETAILED DESCRIPTION

[0041] In order to make the purpose, technical solution and advantages of the present invention clearer, the technical solution of the present invention will be clearly and completely described below in combination with the embodiments of the present invention. Obviously, the described embodiments are part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without making creative work are within the scope of protection of the present invention.

[0042] In a first aspect, the present invention provides a method for preparing a LaOCl-ZnO composite catalyst, the method comprising the following steps:

[0043] (1) calcining lanthanum chloride (LaCl3) in an air atmosphere to obtain lanthanum oxychloride LaOCl;

[0044] (2) mixing LaOCl and zinc nitrate uniformly under ultrasonic conditions with water to obtain a mixed solution, adjusting the pH of the mixed solution to 11-13 (e.g., 11, 12 or 13) with a sodium hydroxide solution (aqueous sodium hydroxide solution), reacting the mixed solution under stirring conditions, and then standing, centrifuging, washing and drying to obtain a LaOCl-ZnO composite catalyst (also referred to as a LaOCl-ZnO composite photocatalyst or a LaOCl-ZnO heterojunction photocatalyst); in the present invention, the stirring is magnetic stirring, and there is no limit on the rotation speed, and reasonable stirring is sufficient; the present invention has no special limitation on the ultrasonic time, for example, the ultrasonic time is 10-30 minutes, based on uniform dispersion; the present invention provides a A method for preparing a LaOCl-ZnO composite catalyst by an ultrasound-assisted in-situ deposition technology. Specifically, in the present invention, LaOCl is first obtained by a one-step calcination method, and then LaOCl and Zn(NO3)2 are uniformly dispersed in deionized water by ultrasound to obtain a mixed solution; the pH of the mixed solution is adjusted using an aqueous NaOH solution and stirred to allow it to react fully, for example, reacting for 0.5 to 1.5 hours under stirring conditions; then standing to allow ZnO nanoparticles to be in-situ deposited on the surface of LaOCl, and finally centrifuging, washing and drying to obtain a LaOCl-ZnO composite catalyst; the LaOCl-ZnO composite catalyst in the present invention is a composite photocatalyst for photocatalytic reduction of uranium.

[0045] Compared with the catalyst doped with lanthanum in ZnO disclosed in the prior art CN110227437A, the ultrasound-assisted in-situ deposition method used in the present invention can keep all active components (ZnO) on the surface of the carrier and disperse them evenly, which greatly improves the utilization rate of the active components. The LaOCl-ZnO composite catalyst material prepared by the present invention has strong photocatalytic redox ability, and the composite structure increases the visible light catalytic activity. The LaOCl-ZnO composite catalyst material has a good application prospect in the photocatalytic treatment of radioactive nuclides.

[0046] LaOCl is a tetragonal layered halogen oxide with excellent photocatalytic performance. n n+ and Cl -Layer composition can be combined with a suitable semiconductor to construct a rectifier diode, which is convenient for separating photoexcited charges. However, LaOCl is a wide bandgap material, which means that it can only absorb near-visible light, which greatly limits its light response range and photocatalytic efficiency. In addition, LaOCl itself has relatively scarce active sites. Nano zinc oxide is considered to be an excellent photocatalytic material that can replace titanium dioxide due to its low cost, easy preparation, and environmental friendliness, but its efficiency in removing uranium as a photocatalyst is low. The present invention creatively proposes and prepares for the first time a new photocatalyst composed of LaOCl and ZnO for photocatalytic reduction of uranium. So far, there has been no report on the study of synthesized LaOCl-ZnO composite catalysts to capture uranium in wastewater.

[0047] The LaOCl-ZnO composite catalyst prepared by the present invention has excellent photocatalytic performance. The present invention deposits nano zinc oxide on LaOCl in situ, thereby broadening the light response range, effectively suppressing the problem of photogenerated electron-hole recombination, and improving the photocatalytic efficiency. Under the synergistic effect of LaOCl and ZnO, the removal rate of uranium is significantly improved. Under visible light irradiation, the adsorption amount of uranium can be as high as 384.5 mg / g, and the removal rate of uranium can be as high as 96.1%. Compared with the hydrothermal method, the in-situ deposition method used in the preparation of the LaOCl-ZnO composite catalyst does not require high temperature and high pressure conditions; compared with the calcination method, the crystal structure is The structure is controllable; the LaOCl-ZnO composite catalyst prepared by the invention has good crystallization effect, and the ultrasound-assisted method promotes the uniform growth of ZnO on the surface of LaOCl; the LaOCl-ZnO composite catalyst prepared by the invention has good photocatalytic reduction of uranium performance, and currently the application of the LaOCl-ZnO composite catalyst in the field of photocatalytic reduction of uranium has not been reported, and the method for preparing the LaOCl-ZnO composite catalyst has the advantages of simple and convenient operation, low cost, low energy consumption and mild conditions, which is conducive to large-scale production, and solves the problems of complex preparation process, high energy consumption in the preparation process and small application range of the materials in the existing photocatalytic materials.

[0048] According to some preferred embodiments, the calcination temperature is 550°C to 700°C (e.g., 550°C, 560°C, 570°C, 580°C, 590°C, 600°C, 610°C, 620°C, 630°C, 640°C, 650°C, 660°C, 670°C, 680°C, 690°C or 700°C), preferably 650°C, and the calcination time is 1.5 to 2.5h (e.g., 1.5, 2 or 2.5h), preferably 2h; in the present invention, more preferably at 650°C LaOCl is prepared by calcination, so that LaOCl with a more complete crystal structure can be obtained. The present invention finds that the complete crystal structure can make LaOCl have better light absorption performance, especially in the visible light region, which is crucial for photocatalytic reactions, because absorbing more light energy can excite more electron-hole pairs, promoting the photocatalytic reaction, and the complete crystal structure is usually accompanied by better electron and hole separation and transfer performance, improving the effective utilization rate of photogenerated electrons and holes, thereby enhancing photocatalytic activity. In addition, the complete crystal structure can provide more catalytic active sites, which helps to promote the photocatalytic reaction more effectively, and the complete crystal structure can make the LaOCl-ZnO composite catalyst more stable, and has good durability for long-term photocatalytic reactions. The present invention finds that the LaOCl-ZnO composite catalyst prepared by calcining LaOCl at 650°C has a significantly stronger ability to photocatalytically reduce uranium.

[0049] According to some preferred embodiments, the zinc nitrate is zinc nitrate hexahydrate (Zn(NO3)2·6H2O); the molar ratio of the LaOCl to the zinc nitrate is 1:(0.5-2) (e.g., 1:0.5, 1:1, 1:1.5 or 1:2); in the present invention, it is preferred to control the molar ratio of LaOCl to zinc nitrate to be 1:(0.5-2), which helps to obtain a LaOCl-ZnO composite catalyst with stronger photocatalytic reduction of uranium and excellent photocatalytic reduction of uranium. The present invention finds that within the molar ratio range of 1:(0.5-2), there is an optimal interaction between LaOCl and zinc nitrate, which helps to form an efficient LaOCl-ZnO composite structure and can achieve optimal electronic Transport and photocatalytic performance, and the appropriate molar ratio can ensure that LaOCl and zinc nitrate fully utilize the active sites on their surfaces, which is helpful to improve the photocatalytic activity, and at an appropriate molar ratio, LaOCl and zinc nitrate are more likely to form a stable composite structure, which is helpful to improve the stability and recycling performance of the photocatalyst. If the molar ratio of LaOCl to zinc nitrate deviates from the range of 1: (0.5-2), it will lead to instability of the composite structure or excessive accumulation of active sites, thereby reducing the catalytic activity of the photocatalyst, and will cause incompleteness of the composite structure, affecting electron transport and photocatalytic performance. In addition, an inappropriate molar ratio will also lead to uneven dispersion between LaOCl and zinc nitrate, affecting the overall performance of the photocatalyst.

[0050] According to some preferred embodiments, the concentration of the sodium hydroxide solution is 0.1-0.3 mol / L (eg, 0.1, 0.2 or 0.3 mol / L).

[0051] According to some preferred embodiments, the ultrasonic time is 20 to 40 minutes, preferably 30 minutes; the standing time is 12 to 30 hours (for example, 12, 14, 16, 18, 20, 22, 24, 26, 28 or 30 hours), preferably 12 to 24 hours; the centrifugal speed is 7000 to 10000 r / min (for example, 7000, 8000, 9000 or 10000 r / min), and the centrifugal time is 4 to 8 minutes, preferably, the centrifugal speed is 8000 r / min, and the centrifugal time is 5 minutes; the washing is carried out by washing with water and / or anhydrous ethanol; and / or the drying temperature is 50 to 80°C (for example, 50°C, 60°C, 70°C or 80°C), preferably 60°C.

[0052] In a second aspect, the present invention provides a LaOCl-ZnO composite catalyst prepared by the preparation method described in the first aspect of the present invention.

[0053] The present invention provides in a third aspect the use of the LaOCl-ZnO composite catalyst prepared by the preparation method described in the first aspect of the present invention in the photocatalytic reduction of uranium, specifically, for example, in the photocatalytic reduction of uranium in uranium-containing wastewater.

[0054] The LaOCl-ZnO composite catalyst provided by the present invention has excellent performance in photocatalytic reduction of uranium, but like the photocatalyst used for photocatalytic reduction of uranium in the prior art, the LaOCl-ZnO composite catalyst in the present invention is also a powder material, and the powder material is difficult to recycle and easily forms secondary pollution.

[0055] In order to solve the above technical problems, the present invention provides a method for preparing LaOCl-ZnO hydrogel in a fourth aspect, the method comprising the following steps:

[0056] (a) using water to uniformly disperse the LaOCl-ZnO composite catalyst prepared by the preparation method described in the first aspect of the present invention by ultrasonication to obtain a LaOCl-ZnO dispersion;

[0057] (b) sodium alginate is added to the LaOCl-ZnO dispersion and mixed uniformly to obtain a LaOCl-ZnO / sodium alginate solution, and then the LaOCl-ZnO / sodium alginate solution is dripped dropwise into a calcium chloride solution, for example, into 100 mL of a 3 wt % calcium chloride aqueous solution and allowed to stand, and finally washed and dried to obtain a LaOCl-ZnO hydrogel (also referred to as SA / LaOCl-ZnO hydrogel microspheres, abbreviated as SLZ or SLZ hydrogel microspheres); the present invention adopts an "embedding" strategy to fix the LaOCl-ZnO composite catalyst in sodium alginate to obtain SA / LaOCl-ZnO hydrogel microspheres, and the prepared LaOCl-ZnO hydrogel is a hydrogel for photocatalytic reduction of uranium.

[0058] In view of the problem that the existing photocatalysts are generally powder materials, which are difficult to recycle and easily form secondary pollution, the present invention adopts sodium alginate (SA), which is a natural anionic polysaccharide with rich functional groups on the surface and easy gelation. The present invention adopts the "embedding" strategy for the first time to prepare the LaOCl-ZnO composite catalyst into LaOCl-ZnO hydrogel, which can solve the problem of difficult recycling of powder materials on the one hand, and further reduce the leaching of ions in the photocatalyst on the other hand, so as to maintain the integrity of the photocatalyst, exert its role to a greater extent, and further improve the photoreduction efficiency of the LaOCl-ZnO composite catalyst to uranium.

[0059] According to some preferred embodiments, the concentration of the LaOCl-ZnO dispersion is 0.0015-0.0025 g / mL (e.g., 0.0015, 0.0016, 0.0017, 0.0018, 0.0019, 0.002, 0.0021, 0.0022, 0.0023, 0.0024 or 0.0025 g / mL), preferably 0.002 g / mL; the mass ratio of the LaOCl-ZnO composite catalyst in step (a) to the sodium alginate in step (b) is 1:(8-12) (e.g., 1:8, 1:8.5, 1:9, 1:9.5, 1:10, 1:10.5, 1:11, 1:11.5 or 1:12), preferably 1:10. The invention found that an appropriate mass ratio can ensure both the effective effect of the photocatalyst and the stability of the hydrogel structure. If the mass ratio of the LaOCl-ZnO composite catalyst to the sodium alginate is inappropriate, the gel network may be unstable or the gel cross-linking density may be too high, thereby reducing the recyclability or limiting the performance of the LaOCl-ZnO photocatalyst; the mass fraction of calcium chloride contained in the calcium chloride solution is 1 to 4% (for example, 1%, 1.5%, 2%, 2.5%, 3%, 3.5% or 4%), preferably 2% to 3%; the amount ratio of the sodium alginate to the calcium chloride solution is 2g: (80 to 120) mL; and / or the standing time is 4 to 8h (for example, 4, 5, 6, 7 or 8h), preferably 6h.

[0060] In a fifth aspect, the present invention provides a LaOCl-ZnO hydrogel prepared by the preparation method described in the fourth aspect of the present invention.

[0061] According to some specific embodiments, the LaOCl-ZnO composite catalyst prepared by the preparation method described in the first aspect of the present invention is embedded in sodium alginate (SA) to obtain SLZ hydrogel, which is used for visible light catalytic rapid capture of uranium in wastewater; the SLZ hydrogel preparation method: weigh 0.2g LaOCl-ZnO composite catalyst and ultrasonically disperse it in 100mL deionized water, then add 2g sodium alginate, stir for 2h to mix evenly; then use a syringe to dropwise add it into a 2% CaCl2 aqueous solution, and let it stand for 6h. Wash with deionized water and vacuum dry to obtain SA / LaOCl-ZnO hydrogel microspheres.

[0062] In a sixth aspect, the present invention provides the use of the LaOCl-ZnO hydrogel prepared by the preparation method described in the fourth aspect of the present invention in the photocatalytic reduction of uranium, specifically, for example, in the photocatalytic reduction of uranium in uranium-containing wastewater.

[0063] According to some preferred embodiments, LaOCl-ZnO hydrogel is added to a U(VI) solution for adsorption under visible light irradiation to achieve photocatalytic reduction of uranium; the concentration of the U(VI) solution is 20 to 700 mg / L (e.g., 20, 50, 100, 150, 200, 250, 300, 350, 400, 450, 500, 550, 600, 650 or 700 mg / L); the adsorption time is 5 to 420 min (e.g., 5, 30, 450, 500, 550, 600, 650 or 700 mg / L); 60, 90, 120, 150, 180, 210, 240, 270, 300, 330, 360, 390 or 420min); in the present invention, the dosage ratio of the LaOCl-ZnO hydrogel to the U(VI) solution is 0.5g:(0.8-1.2)L, preferably 0.5g:1L; the photocatalytic reduction of uranium is carried out under the condition that the pH of the U(VI) solution is 4; the adsorption capacity of LaOCl-ZnO hydrogel for uranium is obtained by the following formula:

[0064] Q e =(C0-C e )×V / m

[0065] Among them, Q e is the adsorption capacity, C0 is the initial concentration of U(VI), in mg / L, C e is the adsorption equilibrium concentration of U(VI), in mg / L, V is the volume of U(VI) solution, in L, and m is the mass of LaOCl-ZnO hydrogel, in g;

[0066] The removal rate of uranium by LaOCl-ZnO hydrogel is obtained by the following formula:

[0067]

[0068] Where C0 is the initial concentration of U(VI), C e is the adsorption equilibrium concentration of U(VI).

[0069] According to some specific implementation methods, the application is: weigh a certain mass of SLZ hydrogel microspheres, add a certain concentration of U(VI) solution, and adsorb for a period of time under visible light conditions; then collect the filtrate, use an inductively coupled plasma mass spectrometer (ICP-MS) to determine the concentration of residual uranyl ions in the filtrate, and use a formula to calculate the adsorption capacity and removal rate of uranium by SLZ hydrogel microspheres, and measure the potential of SA / LaOCl-ZnO hydrogel microspheres for uranium removal from wastewater; preferably, the amount of SLZ hydrogel microspheres added is 0.01 g; preferably, the concentration of the U(VI) solution is 20 to 700 mg / L; preferably, the adsorption time is 5 to 420 min.

[0070] The technical solutions in the embodiments of the present invention are described clearly and completely below. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of them. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0071] Example 1

[0072] This embodiment provides a method for preparing a LaOCl photocatalyst as follows:

[0073] Weigh 1 g of LaCl3 into a crucible, place it directly in a muffle furnace under air atmosphere, and calcine at 550°C for 2 h to obtain a LaOCl photocatalyst.

[0074] Example 2

[0075] This embodiment provides a method for preparing a LaOCl photocatalyst as follows:

[0076] Weigh 1 g of LaCl3 into a crucible, place it directly in a muffle furnace under air atmosphere, and calcine it at 600°C for 2 h to obtain a LaOCl photocatalyst.

[0077] Example 3

[0078] This embodiment provides a method for preparing a LaOCl photocatalyst as follows:

[0079] Weigh 1 g of LaCl3 into a crucible, place it directly in a muffle furnace under air atmosphere, and calcine it at 650°C for 2 h to obtain a LaOCl photocatalyst.

[0080] Example 4

[0081] This embodiment provides a method for preparing a LaOCl photocatalyst as follows:

[0082] Weigh 1 g of LaCl3 into a crucible, place it directly in a muffle furnace under air atmosphere, and calcine it at 700°C for 2 h to obtain a LaOCl photocatalyst.

[0083] The XRD comparison diagram of LaOCl prepared by the present invention and the raw material LaCl3 is as follows: Figure 2As shown in the figure, it can be seen that the diffraction peak of the LaOCl sample is sharp and the material has good crystallinity. Compared with the standard comparison card PDF#82-1200 of LaCl3 and the standard comparison card PDF#88-0064 of LaOCl, the LaOCl sample has obvious diffraction peaks at 12.8°, 25.1°, 30.6°, 33.9°, 40.5°, 43.9°, 50.6°, 51.3°, 56.6° and 58.1°, corresponding to the (001), (101), (110), (102), (112), (200), (113), (211), (212) and (104) crystal planes of lanthanum oxychloride, respectively; indicating that LaCl3 effectively captures oxygen in the air in the air atmosphere, thereby forming LaOCl with good crystallinity.

[0084] The XRD patterns of the LaOCl photocatalysts obtained by calcining at different temperatures in Examples 1 to 4 of the present invention are as follows: Figure 3 As shown in the figure, it can be seen that with the increase of temperature, the crystal structure of LaOCl becomes more complete. This shows that LaOCl has excellent thermal stability. However, too high a temperature will lead to an unstable structure. Therefore, 650℃ was finally selected as the optimal calcination temperature.

[0085] Example 5

[0086] This embodiment provides a method for preparing a LaOCl-ZnO composite catalyst as follows:

[0087] Take LaOCl and zinc nitrate hexahydrate (Zn(NO3)2·6H2O) prepared by calcining at 650°C according to the method in Example 3 as raw materials; dissolve LaOCl and zinc nitrate hexahydrate in 100mL deionized water at a molar ratio of 1:0.5, and ultrasonically disperse for 30 minutes to obtain a mixed solution, wherein the sum of the mass percentages of LaOCl and zinc nitrate hexahydrate in the mixed solution is 3.38%, and use a 0.2mol / L NaOH aqueous solution to adjust the pH of the mixed solution to 12 and stir it to fully react for 1 hour, let it stand for 12 hours, so that nano zinc oxide ZnO particles are in situ deposited on the surface of LaOCl, and finally centrifuge, wash and dry to obtain a LaOCl-ZnO composite catalyst (referred to as LaOCl-ZnO-0.5); the centrifugal speed is 8000r / min, the centrifugal time is 5min, the washing is washing with deionized water and anhydrous ethanol in sequence, and the drying is drying at 60°C for 12 hours.

[0088] Example 6

[0089] This embodiment provides a method for preparing a LaOCl-ZnO composite catalyst as follows:

[0090] Take LaOCl and zinc nitrate hexahydrate (Zn(NO3)2·6H2O) prepared by calcining at 650°C according to the method in Example 3 as raw materials; dissolve LaOCl and zinc nitrate hexahydrate in 100mL deionized water at a molar ratio of 1:1, and ultrasonically disperse for 30 minutes to obtain a mixed solution, wherein the sum of the mass percentages of LaOCl and zinc nitrate hexahydrate in the mixed solution is 3.38%, use a 0.2mol / L NaOH aqueous solution to adjust the pH of the mixed solution to 12 and stir to fully react for 1 hour, let it stand for 12 hours to allow nano zinc oxide ZnO particles to be in situ deposited on the surface of LaOCl, and finally centrifuge, wash and dry to obtain a LaOCl-ZnO composite catalyst (referred to as LaOCl-ZnO-1); the centrifugal speed is 8000r / min, the centrifugal time is 5min, the washing is washing with deionized water and anhydrous ethanol in sequence, and the drying is drying at 60°C for 12 hours.

[0091] Example 7

[0092] This embodiment provides a method for preparing a LaOCl-ZnO composite catalyst as follows:

[0093] Take LaOCl and zinc nitrate hexahydrate (Zn(NO3)2·6H2O) prepared by calcining at 650°C according to the method in Example 3 as raw materials; dissolve LaOCl and zinc nitrate hexahydrate in 100mL deionized water at a molar ratio of 1:1.5, and ultrasonically disperse for 30 minutes to obtain a mixed solution, wherein the sum of the mass percentages of LaOCl and zinc nitrate hexahydrate in the mixed solution is 3.38%, and use a 0.2mol / L NaOH aqueous solution to adjust the pH of the mixed solution to 12 and stir to fully react for 1 hour, and let it stand for 12 hours to allow nano zinc oxide ZnO particles to be in situ deposited on the surface of LaOCl, and finally centrifuge, wash and dry to obtain a LaOCl-ZnO composite catalyst (referred to as LaOCl-ZnO-1.5); the centrifugal speed is 8000r / min, the centrifugal time is 5min, the washing is washing with deionized water and anhydrous ethanol in sequence, and the drying is drying at 60°C for 12 hours.

[0094] Example 8

[0095] This embodiment provides a method for preparing a LaOCl-ZnO composite catalyst as follows:

[0096] Take LaOCl and zinc nitrate hexahydrate (Zn(NO3)2·6H2O) prepared by calcining at 650°C according to the method in Example 3 as raw materials; dissolve LaOCl and zinc nitrate hexahydrate in 100mL deionized water at a molar ratio of 1:2, and ultrasonically disperse for 30 minutes to obtain a mixed solution, wherein the sum of the mass percentages of LaOCl and zinc nitrate hexahydrate in the mixed solution is 3.38%, and use a 0.2mol / L NaOH aqueous solution to adjust the pH of the mixed solution to 12 and stir it to fully react for 1 hour, let it stand for 12 hours, so that nano zinc oxide ZnO particles are in situ deposited on the surface of LaOCl, and finally centrifuge, wash and dry to obtain a LaOCl-ZnO composite catalyst (referred to as LaOCl-ZnO-2); the centrifugal speed is 8000r / min, the centrifugal time is 5min, the washing is washing with deionized water and anhydrous ethanol in sequence, and the drying is drying at 60°C for 12 hours.

[0097] The XRD analysis patterns of the LaOCl-ZnO-x (x=0.5, 1, 1.5, 2) composite photocatalysts prepared by ultrasound-assisted in-situ deposition method in Examples 5 to 8 of the present invention are as follows: Figure 4 As shown in the figure, it can be seen that as the proportion of ZnO increases, the peak intensity of the three main diffraction peaks at 31.7°, 34.3° and 36.2° corresponding to the (100), (002) and (101) crystal planes of ZnO gradually increases. The composite photocatalyst material has high crystallinity and no impurity phase in the material, indicating that the ultrasound-assisted in-situ deposition method enables ZnO to be fully grown on LaOCl.

[0098] The SEM-DES images of the LaOCl-ZnO composite catalysts prepared in Examples 5 to 8 of the present invention are as follows: Figure 5 As shown. Figure 5 (a) The LaOCl prepared by the one-step calcination method exhibits a layered structure, which provides a site for the deposition of ZnO. Figure 5 In (b), ZnO presents a flower-like structure and has good crystallization effect, which is consistent with the XRD analysis. Figure 5 (c)-(f) are SEM images of LaOCl-ZnO (0.5, 1, 1.5, 2), respectively. It can be seen that as the content of ZnO increases, the ZnO structure on the LaOCl layered structure becomes more perfect and the flower-like structure is evenly dispersed. This not only proves the successful preparation of the composite photocatalyst using ultrasound-assisted in-situ deposition, but also that this method successfully retains the active component ZnO completely on LaOCl. This once again highlights the superiority of this method over other preparation methods. Figure 5(g) is the EDS spectrum of SLZ-1.5. It is obvious that La, O, Zn and Cl elements are evenly distributed, which once again proves that ZnO is evenly deposited on LaOCl to form a heterojunction structure. The photocatalytic performance characterization results of the LaOCl-ZnO composite catalysts prepared in Examples 5 to 8 of the present invention are shown in Figure 1. Figure 7 and Figure 8 as shown; Figure 7 (a) to Figure 7 (c) Photoinduced electrons (e) were analyzed by PL fluorescence spectroscopy and electrochemical impedance spectroscopy (EIS). - ) and holes (h + ) separation efficiency, Figure 7 (a) shows the EIS spectra of ZnO, LaOCl, and LaOCl-ZnO-1.5, among which the impedance curve of LaOCl-ZnO-1.5 shows the smallest arc radius, which further proves that it has the highest photogenerated - and h + Separation efficiency, such as Figure 7 As shown in (b), LaOCl has a very high fluorescence intensity, indicating that the degree of recombination of photogenerated electron-hole pairs is high. In contrast, the fluorescence intensity of LaOCl-ZnO-1.5 is the weakest, indicating that the recombination of photogenerated electrons in the LaOCl-ZnO-1.5 heterojunction is effectively suppressed. Figure 7 (c) The band gaps (E) of LaOCl, ZnO and LaOCl-ZnO-1.5 were calculated using the Kubelka-Munk equation. g ) are 3.21eV, 3.08eV and 3.17eV respectively. In addition, Figure 8 As shown in (a)-8(c), the Mott-Schottky (MS) curves of LaOCl, ZnO and LaOCl-ZnO-1.5 were obtained using an electrochemical workstation, and the valence bands (CB) of ZnO, LaOCl and LaOCl-ZnO-1.5 were calculated to be -0.83, -0.28 and -0.52 eV, respectively, and the formula E g =E VB +E CB The calculated VB are 2.91, 2.24 and 2.65 eV respectively. The energy band structure diagram is constructed according to the position of the conduction band and valence band, as shown in Figure 8 (d) Therefore, the photoreduction of U(VI) by LaOCl-ZnO-1.5 is feasible because the E CB Higher than UO2 2+ / UO2(0.441eV) and UO2 2+ / U 4+Based on the above results, we believe that the excellent photocatalytic performance of LaOCl-ZnO-1.5 is attributed to its strong absorption capacity of visible light and suitable band gap; Figure 4 , Figure 5 , Figure 7 and Figure 8 The performance test is shown in Table 1 below. The preparation of the nano zinc oxide ZnO is as follows: zinc nitrate hexahydrate is dissolved in 100 mL of deionized water, and ultrasonically dispersed for 30 min to obtain a mixed solution, wherein the mass percentage of zinc nitrate hexahydrate in the mixed solution is 3.38%, a 0.2 mol / L NaOH aqueous solution is used to adjust the pH of the mixed solution to 12 and stir it to fully react for 1 h, and stand it for 12 h to allow the nano zinc oxide ZnO to precipitate, and finally centrifuge, wash and dry to obtain nano zinc oxide ZnO; the centrifugal speed is 8000 r / min, the centrifugal time is 5 min, the washing is sequentially washed with deionized water and anhydrous ethanol, and the drying is dried at 60° C. for 12 h.

[0099] Example 9

[0100] This embodiment provides a method for preparing LaOCl-ZnO hydrogel (SA / LaOCl-ZnO hydrogel microspheres) as follows:

[0101] 0.2 g of the LaOCl-ZnO composite catalyst (LaOCl-ZnO-1.5) prepared according to the method in Example 7 was dispersed in 100 mL of deionized water by ultrasound for 10 min, and then 2 g of sodium alginate (SA) was added and stirred for 2 h to mix evenly to obtain a LaOCl-ZnO / sodium alginate solution. The LaOCl-ZnO / sodium alginate solution was then dripped dropwise into 100 mL of a 3% CaCl2 aqueous solution through a syringe and allowed to stand for 6 h to fully gel. Finally, the sample was washed with deionized water and dried in vacuo at 60°C for 12 h to obtain SA / LaOCl-ZnO hydrogel microspheres (denoted as SLZ-1.5).

[0102] The SEM image of SA / LaOCl-ZnO-1.5 hydrogel microspheres prepared in Example 9 of the present invention is as follows: Figure 6 shown; from Figure 6It can be seen that a large number of grooves are distributed on the surface of the gel, and the rough surface is conducive to expanding the specific surface area, thereby more efficiently capturing uranyl ions. It is worth noting that the coated LaOCl-ZnO composite catalyst can be observed on the surface of the microspheres, which greatly reduces the dose loss of the photocatalyst, improves its utilization efficiency, and enhances the photocatalytic effect. In the present invention, 0.01 g of SLZ hydrogel microspheres (SLZ-1.5) are weighed and added to a concentration of 200 mg / L, 20 mL of U (VI) solution of different pH values, and adsorbed for 12 hours at room temperature T = 298K, without light, and under visible light (1 sun intensity). The filtrate is collected and the concentration of the remaining uranyl ions in the filtrate is determined using an inductively coupled plasma mass spectrometer (ICP-MS), and the adsorption capacity and removal rate of uranium by SLZ hydrogel microspheres are calculated using a formula; the present invention studies and compares the effects of different pH values ​​on the adsorption of uranium by SLZ-1.5, and the results are as follows: Fig. 9 as shown; Fig. 9 As shown in the figure, the optimal pH value of SLZ-1.5 with or without light is 4. Without light, the adsorption of uranium by SLZ-1.5 at pH = 4 is 323.3 mg / g, and the removal rate is 80.8%. After light, the adsorption of uranium by SLZ-1.5 increased to 384.5 mg / g, and the removal rate reached 96.1%. Compared with the no light condition, the removal rate increased by 15.3%. It shows that the synergistic effect of photocatalytic reduction and adsorption effectively promotes the capture of uranium by SLZ-1.5.

[0103] The present invention studied the adsorption-photocatalytic kinetics and isotherm of uranium by SLZ-1.5 at pH = 4 under light and dark contrast. Fig.10 as shown; Fig.10 As shown in (a), it is obvious that the photocatalytic effect not only improves the adsorption capacity of SLZ-1.5 for uranium, but also increases the capture rate of uranium; under lightless conditions, SLZ-1.5 tends to adsorption equilibrium in more than 4 hours. Under visible light irradiation, SLZ-1.5 tends to adsorption equilibrium in 130 minutes; this is attributed to the synergistic effect of photocatalytic reduction and adsorption, which improves the selectivity of the material for uranyl ions and enables it to quickly capture uranyl ions. Secondly, the adsorption data of SLZ-1.5 were fitted using pseudo-second-order kinetics. Fig.10 As shown in (b), pseudo-second-order kinetics can better describe the adsorption process of uranium by SLZ-1.5, indicating that chemical adsorption is the limiting factor of the rate-controlling step. In addition, the Langmuir and Freundlich isotherm models were used to fit the adsorption data, as shown in Fig.10 (c) and Fig.10(d) As shown. Obviously, Langmuir can better describe the adsorption process, indicating that the adsorption of uranium by SLZ-1.5 is a single-layer adsorption. The Langmuir maximum adsorption of SLZ-1.5 under no light conditions and light conditions is 602.78 mg / g and 905.1 mg / g respectively. The fitting calculation formula is as follows:

[0104] Q e = b·Q L ·C e / (1+b·C e )

[0105] Where b (L / mg) is the equilibrium constant; Q L (mg / g) is the monolayer saturated adsorption capacity, where “1” is the number “1”.

[0106] Example 10

[0107] Take LaOCl and zinc nitrate hexahydrate (Zn(NO3)2·6H2O) prepared by calcining at 550°C according to the method in Example 1 as raw materials; dissolve LaOCl and zinc nitrate hexahydrate in 100mL deionized water at a molar ratio of 1:1.5, and ultrasonically disperse for 30 minutes to obtain a mixed solution, wherein the sum of the mass percentages of LaOCl and zinc nitrate hexahydrate in the mixed solution is 3.38%, use a 0.2mol / L NaOH aqueous solution to adjust the pH of the mixed solution to 12 and stir to fully react for 1 hour, let it stand for 12 hours to allow nano zinc oxide ZnO particles to be in situ deposited on the surface of LaOCl, and finally centrifuge, wash and dry to obtain a LaOCl-ZnO composite catalyst; the centrifuge speed is 8000r / min, the centrifuge time is 5min, the washing is washing with deionized water and anhydrous ethanol in sequence, and the drying is drying at 60°C for 24 hours.

[0108] 0.2 g of the LaOCl-ZnO composite catalyst prepared according to the above method was dispersed in 100 mL of deionized water by ultrasound for 10 min, and then 2 g of sodium alginate (SA) was added and stirred for 2 h to mix evenly to obtain a LaOCl-ZnO / sodium alginate solution. The LaOCl-ZnO / sodium alginate solution was then dripped dropwise into a 3% CaCl2 aqueous solution through a syringe and allowed to stand for 6 h to fully gel. Finally, the sample was washed with deionized water and dried in vacuum at 60°C for 12 h to obtain SA / LaOCl-ZnO hydrogel microspheres.

[0109] Embodiment 11

[0110] Example 11 is substantially the same as Example 10, except that:

[0111] LaOCl prepared by calcining at 600° C. according to the method in Example 2 and zinc nitrate hexahydrate (Zn(NO 3 ) 2 ·6H 2 O) were used as raw materials to prepare LaOCl-ZnO composite catalyst, and then SA / LaOCl-ZnO hydrogel microspheres were obtained.

[0112] Example 12

[0113] Example 12 is substantially the same as Example 10, except that:

[0114] LaOCl prepared by calcining at 700° C. according to the method in Example 4 and zinc nitrate hexahydrate (Zn(NO 3 ) 2 ·6H 2 O) were used as raw materials to prepare LaOCl-ZnO composite catalyst, and then SA / LaOCl-ZnO hydrogel microspheres were obtained.

[0115] Embodiment 13

[0116] Take LaOCl and zinc nitrate hexahydrate (Zn(NO3)2·6H2O) prepared by calcining at 650°C according to the method in Example 3 as raw materials; dissolve LaOCl and zinc nitrate hexahydrate in 100mL deionized water at a molar ratio of 1:0.3, and ultrasonically disperse for 30 minutes to obtain a mixed solution, wherein the sum of the mass percentages of LaOCl and zinc nitrate hexahydrate in the mixed solution is 3.38%, use a 0.2mol / L NaOH aqueous solution to adjust the pH of the mixed solution to 12 and stir to fully react for 1 hour, let it stand for 12 hours to allow nano zinc oxide ZnO particles to be in situ deposited on the surface of LaOCl, and finally centrifuge, wash and dry to obtain a LaOCl-ZnO composite catalyst; the centrifugal speed is 8000r / min, the centrifugal time is 5min, the washing is washing with deionized water and anhydrous ethanol in sequence, and the drying is drying at 60°C for 12 hours.

[0117] 0.2 g of the LaOCl-ZnO composite catalyst prepared according to the above method was dispersed in 100 mL of deionized water by ultrasound for 10 min, and then 2 g of sodium alginate (SA) was added and stirred for 2 h to mix evenly to obtain a LaOCl-ZnO / sodium alginate solution. The LaOCl-ZnO / sodium alginate solution was then dripped dropwise into a 3% CaCl2 aqueous solution through a syringe and allowed to stand for 6 h to fully gel. Finally, the sample was washed with deionized water and dried in vacuum at 60°C for 12 h to obtain SA / LaOCl-ZnO hydrogel microspheres.

[0118] Embodiment 14

[0119] Example 14 is substantially the same as Example 13, except that:

[0120] LaOCl and zinc nitrate hexahydrate were dissolved in 100 mL of deionized water at a molar ratio of 1:2.5, and ultrasonically dispersed for 30 min to obtain a mixed solution.

[0121] Comparative Example 1

[0122] Add 3mmol / mL NaOH aqueous solution dropwise to 20mL 3mmol / mL Zn(NO3)2·6H2O aqueous solution to generate white precipitate, add 0.1g KCl and stir on a stirrer for 10min, then add La(NO3)3·6H2O to the mixture to make the molar ratio of La to Zn 1:1.5, continue stirring for 30min, transfer the mixture to a polytetrafluoroethylene reactor, place it in a 100℃ forced air drying oven for reaction for 2h. After cooling to room temperature, centrifuge, wash with deionized water and anhydrous ethanol several times, dry at 40℃ for use, and obtain LaOCl-ZnO composite catalyst.

[0123] Comparative Example 2

[0124] Add 3mmol / mL NaOH aqueous solution dropwise to 20mL 3mmol / mL Zn(NO3)2·6H2O aqueous solution to generate white precipitate, add 0.1g KCl and stir on a stirrer for 10min, then add Bi(NO3)3·5H2O to the mixture to make the molar ratio of Bi to Zn 1:1, continue stirring for 30min, transfer the mixture to a polytetrafluoroethylene reactor, place it in a 100℃ forced air drying oven to react for 2h. After cooling to room temperature, centrifuge, wash with deionized water and anhydrous ethanol several times, dry at 40℃ for use, and obtain BiOCl-ZnO composite photocatalyst.

[0125] Comparative Example 3

[0126] Lanthanum acetate and zinc acetate were added to 100 mL of distilled water for dissolution, so that the molar percentage of La to Zn was 0.03%. After 40 minutes of magnetic stirring, the solution pH was adjusted to 9 with concentrated ammonia water. After stirring for 5 minutes, it was transferred to a hydrothermal synthesis reactor and placed in a blast oven at 100°C for hydrothermal reaction for 12 hours. After the reaction was completed, the precipitate was filtered and washed alternately with distilled water and anhydrous ethanol for 3 times, and then dried and ground in a blast oven at 60°C to obtain a lanthanum-doped zinc oxide catalyst precursor. Then it was placed in a muffle furnace and calcined at 400°C for 2 hours to obtain a La-doped ZnO catalyst.

[0127] Comparative Example 4

[0128] A method for preparing erbium-doped zinc oxide nanosheets based on photocatalytic reduction of uranium comprises the following steps:

[0129] Step 1: Disperse 3.7 g (99%, AR, 12.4 mmol) Zn(NO3)2·6H2O and 1.72 g hexamethylenetetramine (HMT) in 50 mL of water. After stirring, add 10 mL of single-layer graphene oxide solution (0.02 g of single-layer graphene oxide is ultrasonically dissolved in 30 mL of deionized water) and 0.5 mL of erbium chloride hexahydrate solution (concentration is 1 M) to obtain a mixed solution.

[0130] Step 2: Add the mixed solution into a 100 mL Teflon-lined autoclave and react at 150° C. for 24 h; wash the obtained sample with ethanol and centrifuge it, and then dry it at 60° C. for 12 h;

[0131] Step 3: anneal the dried sample at 800 °C for 2 h to obtain erbium-doped zinc oxide nanosheets (Er 0.04 -ZnO).

[0132] Weigh the Er obtained in this comparative example 0.04 -ZnO sample 0.01g was added into 20mL U(VI) solution with a concentration of 200mg / L and pH=4, and adsorbed for 12h in the absence of light. The adsorption amount and removal rate of uranium were measured to be 226.28mg / g and 56.7% respectively.

[0133] The SA / LaOCl-ZnO hydrogel microspheres (test samples) prepared in Examples 9 to 14, the LaOCl-ZnO composite catalyst (test sample) prepared in Example 7, and the catalysts (test samples) prepared in Comparative Examples 1 to 3 were evaluated for photocatalytic reduction of uranium. The test method was:

[0134] 0.01 g of the sample to be tested was weighed and added into a U(VI) solution with a concentration of 200 mg / L, 20 mL, and pH = 4. The solution was adsorbed under visible light (1 sun intensity) for 4 h. The adsorption amount and removal rate of uranium were measured and the results are shown in Table 1. The present invention also uses the same test method to evaluate the photocatalytic reduction uranium performance of the LaOCl photocatalyst and ZnO nanopowder prepared in Example 3.

[0135] Table 1

[0136] sample Adsorption capacity (mg / g) Removal rate (%) Example 9 384.5 96.10% Example 10 250.6 62.65% Embodiment 11 301.1 75.27% Example 12 263.4 65.85% Embodiment 13 183.4 45.85% Embodiment 14 235.5 58.87% Comparative Example 1 333.3 83.33% Comparative Example 2 294.1 73.52% Comparative Example 3 322.7 80.67% LaOCl-ZnO composite catalyst 344.6 86.15% LaOCl 172.2 43.05% ZnO 168.6 42.15%

[0137] In Table 1, “LaOCl-ZnO composite catalyst” is the sample prepared in Example 7, and “LaOCl” is the sample prepared in Example 3.

[0138] Comparing the adsorption amounts of the examples and comparative examples in Table 1, it is shown that the SA / LaOCl-ZnO-1.5 hydrogel obtained in Example 9 has the best adsorption effect, highlighting the advantages of the photocatalyst prepared by the ultrasound-assisted in-situ deposition method and the SLZ hydrogel over other implementation schemes: 1. The preparation method is innovative. The ultrasound-assisted in-situ deposition method is simple to operate, low in energy consumption, and does not require high temperature and harsh conditions. 2. Powdered nano zinc oxide easily reacts and decomposes under acidic conditions, which makes it poorly recyclable. The LaOCl-ZnO prepared by the ultrasound-assisted in-situ deposition method and the SLZ hydrogel prepared by the embedding strategy effectively alleviate this problem. Fig.11 The SLZ hydrogel shown still maintains a removal rate of 93.2% after 5 cycles, with basically no attenuation. 3. Powdered nano zinc oxide is difficult to recycle during the adsorption process, which can easily cause secondary pollution problems. However, SLZ hydrogel effectively solves the hidden dangers brought about by this problem. 4. This material not only achieves efficient capture of uranium under light conditions, but also has a higher adsorption capacity (80.8%) under dark conditions compared to the low adsorption effect of most photocatalysts under dark conditions, and is expected to achieve all-weather adsorption. Therefore, this material can be better used in the actual wastewater uranium removal process.

[0139] The present invention also uses the SA / LaOCl-ZnO hydrogel microspheres prepared in Example 9 for cyclic photocatalytic reduction of uranium. Each time, the SA / LaOCl-ZnO hydrogel microspheres are adsorbed for 4 hours according to the photocatalytic reduction of uranium test method of the present invention. After filtering the SA / LaOCl-ZnO hydrogel microspheres, they are soaked in 0.1M HNO3 solution for 4 hours to achieve a desorption effect, and then the remaining HNO3 on the surface of the material is washed with water, and vacuum dried at 60°C for 6 hours to obtain the SA / LaOCl-ZnO hydrogel microspheres after the first cycle. The SA / LaOCl-ZnO hydrogel microspheres are recovered according to this method, and the photocatalytic reduction of uranium test is repeated 5 times to obtain the fifth removal rate result, as shown in FIG. Fig.11 As shown in Table 2, the removal rate obtained by the first photocatalytic reduction of uranium in Table 2 is recorded as the first removal rate.

[0140] Table 2

[0141]

[0142] Parts of the present invention that are not described in detail are well known to those skilled in the art.

[0143] Finally, it should be noted that: the above is a detailed introduction to the efficient LaOCl-ZnO composite catalyst, preparation method and application disclosed in the embodiments of the present invention. Specific examples are used in this article to illustrate the implementation methods of the present invention. The description of the above embodiments is only used to help understand the method of the present invention and its core idea. At the same time, for those skilled in the art, according to the idea of ​​the present invention, there will be changes in the specific implementation methods and application scopes. In summary, the content of this specification should not be understood as limiting the present invention. Although the present invention is described in detail with reference to the aforementioned embodiments, those skilled in the art should understand that they can still modify the technical solutions recorded in the aforementioned embodiments, or replace some of the technical features therein with equivalents. These modifications or replacements do not deviate the essence of the corresponding technical solutions from the spirit and scope of the technical solutions of the embodiments of the present invention.

Claims

1. A method for preparing a LaOCl-ZnO composite catalyst, characterized in that: The method comprises the following steps: (1) calcining lanthanum chloride in an air atmosphere to obtain LaOCl; (2) LaOCl and zinc nitrate are uniformly mixed with water under ultrasonic conditions to obtain a mixed solution, the pH of the mixed solution is adjusted to 11-13 with a sodium hydroxide solution and reacted under stirring conditions, and then allowed to stand, centrifuged, washed and dried to obtain a LaOCl-ZnO composite catalyst.

2. The preparation method according to claim 1, characterized in that: The calcination temperature is 550°C to 700°C, and the calcination time is 1.5 to 2.5 hours; The zinc nitrate is zinc nitrate hexahydrate; The molar ratio of the LaOCl to the zinc nitrate is 1:(0.5-2); and / or The concentration of the sodium hydroxide solution is 0.1-0.3 mol / L.

3. The preparation method according to claim 2, characterized in that: The calcination temperature is 650° C., and the calcination time is 2 h.

4. The preparation method according to claim 1, characterized in that: The standing time is 12 to 30 hours; The centrifugal speed is 7000-10000 r / min, and the centrifugal time is 4-8 min; The washing is performed by using water and / or anhydrous ethanol; and / or The drying temperature is 50-80°C.

5. The preparation method according to claim 4, characterized in that: The standing time is 12 to 24 hours, the centrifugal speed is 8000 r / min, and the centrifugal time is 5 minutes; and / or The drying temperature is 60°C.

6. A LaOCl-ZnO composite catalyst prepared by the preparation method according to any one of claims 1 to 5.

7. Use of the LaOCl-ZnO composite catalyst prepared by the preparation method according to any one of claims 1 to 5 in catalytic reduction of uranium.

8. A method for preparing LaOCl-ZnO hydrogel, characterized in that: The method comprises the following steps: (a) uniformly dispersing the LaOCl-ZnO composite catalyst prepared by the preparation method according to any one of claims 1 to 5 by ultrasonication with water to obtain a LaOCl-ZnO dispersion; (b) adding sodium alginate to the LaOCl-ZnO dispersion and mixing them uniformly to obtain a LaOCl-ZnO / sodium alginate solution, then dropping the LaOCl-ZnO / sodium alginate solution into a calcium chloride solution and allowing the solution to stand, and finally washing and drying to obtain a LaOCl-ZnO hydrogel.

9. The preparation method according to claim 8, characterized in that: The concentration of the LaOCl-ZnO dispersion is 0.0015 to 0.0025 g / mL; The mass ratio of the LaOCl-ZnO composite catalyst in step (a) to the sodium alginate in step (b) is 1:(8-12); The mass fraction of calcium chloride contained in the calcium chloride solution is 1 to 4%; and / or The standing time is 4 to 8 hours.

10. The preparation method according to claim 9, characterized in that: The concentration of the LaOCl-ZnO dispersion is 0.002 g / mL; The mass ratio of the LaOCl-ZnO composite catalyst in step (a) to the sodium alginate in step (b) is 1:10; The mass fraction of calcium chloride contained in the calcium chloride solution is 2% to 3%; and / or The standing time is 6 hours.

11. LaOCl-ZnO hydrogel prepared by the preparation method according to claim 8 or 9.

12. Use of the LaOCl-ZnO hydrogel prepared by the preparation method according to claim 8 or 9 in catalytic reduction of uranium.

13. The use according to claim 12, characterized in that: LaOCl-ZnO hydrogel was added to U(VI) solution and adsorbed under visible light to achieve catalytic reduction of uranium; The concentration of the U(VI) solution is 20-700 mg / L; The adsorption time is 5 to 420 minutes; The adsorption capacity of LaOCl-ZnO hydrogel for uranium is obtained by the following formula: Q e =(C0-C e )×V / m Among them, Q e is the adsorption capacity, C0 is the initial concentration of U(VI), in mg / L, C e is the adsorption equilibrium concentration of U(VI), in mg / L, V is the volume of U(VI) solution, in L, and m is the mass of LaOCl-ZnO hydrogel, in g; The removal rate of uranium by LaOCl-ZnO hydrogel is obtained by the following formula: Where C0 is the initial concentration of U(VI), C e is the adsorption equilibrium concentration of U(VI).

Citation Information

Patent Citations

  • La-doped ZnO catalyst, preparation method and application thereof

    CN110227437A